Дослідження шляхів підвищення ефективності діяльності підприємства - Погорєлов, Сергій Миколайович; Леденко, О. В.; Матяж, О. А. (НТУ "ХПІ", 2015)
Становлення ринкової системи господарювання та розвиток досконалих конкурентних відносин між її суб’єктами в Україні вимагають впровадження одночасно керівного та керованого організаційно-економічного механізму. У статті висвітлено основні поняття ефективності роботи підприємства. Розглянуто групи показників системи економічної ефективності діяльності та визначено основні шляхи підвищення ефективності роботи підприємства.

There is reflected in the article the basic concepts of enterprise performance. There are considered the indicators group of economic activity system and the main ways of improving the efficiency of the company are identified. Efficiency (activity) company - is a complex concept that reflects the final results of the use of resources over time, the main feature of which may be the need to achieve the goal of industrial and economic activities with the least expenditure of social labor or time. Successful implementation of development strategy provides for effective, efficient and competitive business.
Research of ways of increase of efficiency of enterprise activity
Keywords: результативність; конкурентоспроможність; розвиток підприємства; организаційно-економічний механізм; efficiency; productivity; competitiveness; enterprise development